2010
DOI: 10.1002/ptr.3071
|View full text |Cite
|
Sign up to set email alerts
|

Bioguided isolation of angiotensin‐converting enzyme inhibitors from the seeds of Plantago asiatica L.

Abstract: Ethanolic extract of the seeds of Plantago asiatica L. showed significant inhibitory activity of angiotensin-converting enzyme (ACE) determined by monitoring the transformation from a substrate hippuryl-histidyl-leucine (HHL) to the product hippuric acid (HA) in vitro using an UPLC-MS method. The bioguided fractionation of the extract resulted in the isolation of four ACE inhibitory active phenylpropanoid glycosides acteoside, isoacteoside, plantainoside D, and plantamajoside with IC(50) values of 2.69 mM, 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 11 publications
(13 reference statements)
1
35
0
Order By: Relevance
“…Modern pharmacological studies have proven that Cheqian can be used as a diuretic and antihypertensive, and a methanol extract of Cheqian was found to have dosedependent glycation inhibitory activity and hepatoprotective effect. Cheqian essential oils have also shown hypocholesterolemic properties in mice through suppressing the expression of HMG-CoA reductase in vitro [13][14][15][16].…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…Modern pharmacological studies have proven that Cheqian can be used as a diuretic and antihypertensive, and a methanol extract of Cheqian was found to have dosedependent glycation inhibitory activity and hepatoprotective effect. Cheqian essential oils have also shown hypocholesterolemic properties in mice through suppressing the expression of HMG-CoA reductase in vitro [13][14][15][16].…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…hongyao, Picrorhiza scrophulariiflora, Digitalis purpurea, and Penstemon linariodes showed antihypertensive, antioxidant, anti-inflammatory, and chemopreventive activities. 17,[26][27][28][29] In this study, we demonstrate the beneficial effect of PAS and one of its compounds, plantainoside D, in HDFs which could be developed as a topical agent used to prevent and treat skin aging. Treatment of HDFs with PAS extract decreased UV-induced expression of MMP-1 (Figure 1(a) and (b)), reduced wrinkle formation (Figure 2(a)), and restored collagen content in vivo (Figure 3(a)).…”
Section: Articlementioning
confidence: 99%
“…15 PAS contains fatty acid, polysaccharides, aucubin, geniposidic acid, and phenylpropanoid glycosides as its main components. 16,17 It has been reported that the main components of the herb, such as the phenylethanoid glycoside plantamajoside, the flavonoid glycosides plantagin, and the irridoid glycoside aucubin, possess antibacterial, antiallergic, anti-inflammatory, antioxidation, and lipoxygenase inhibitory activities. 18 In this study, we investigated whether the topical application of PAS extract prevents UV-induced skin damage and attenuates the features of photoaging in mice.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The ACE activity of a product in vitro is usually evaluated by monitoring its effect on the catalytic transformation of a substrate. Recent reports on medicinal plants containing phenylethanoid glycosides list signicant therapeutic effects on hypertension, due mainly to their ACE inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%